Modern requirements for the construction of sports facilities in the context of sustainable development - Melnyk, V.; Zgalat-Lozynska, L. (Ways to Improve Construction Efficiency, 2024)
In the context of global economic, environmental and social challenges, sustainable development is of particular importance in all areas of activity, including construction. Sports facilities, as part of the infrastructure of cities and regions, are no exception and must meet modern requirements that help to increase economic efficiency, reduce maintenance and operating costs, conserve natural resources, minimize negative environmental impacts, and ensure comfort and safety for users. The issue of sustainable construction of sports facilities is becoming increasingly relevant as there is a growing need for integrated approaches to the design and operation of such facilities that meet the requirements of energy efficiency, environmental safety and economic viability. As sports facilities tend to be large and long-lived, they need to be designed and built with the latest advances in energy efficiency, renewable energy sources, and environmental and social balance in mind. An important aspect is not only the use of modern technologies, but also the integration of such facilities into the urban environment, creating conditions for convenient access and active interaction with the local community. The article discusses the basic principles, innovative approaches to the design and construction of sports facilities, as well as modern requirements for their design and operation in the context of achieving sustainable development goals. The authors emphasize the importance of creative and functional design of sports facilities, which allows creating multifunctional facilities that can be used for various activities throughout the year. Such facilities help to popularize sports, attract a wide audience, stimulate economic development and have a positive impact on the image of cities and regions. The authors focus on the importance of an integrated design approach that considers flexibility, safety, environmental friendliness, practicality, technological innovation and aesthetic appeal.